PERANCANGAN PERANGKAT LUNAK PEMBELAJARAN AUTHENTICATION DAN DIGITAL SIGNATURE SCHEME DENGAN METODE SIMULASI SCHNORR - HOTLER MANURUNG (Jurnal Informatika Kaputama (JIK), 2019)
At present, data or information security is very important to be carried out by various parties who communicate with each other, where security in the data transmission process has developed quite rapidly, one of which is cryptography. In computer lectures, cryptography is one of the courses taught. Cryptographic learning becomes very important for computer students to know the ways to secure data. In writing this research, we will explain how to secure data using Schnorr simulation through a learning media. The important points in this simulation are how to find out the procedures or processes carried out in key formation, authentication and digital signatures. The purpose of making this learning media application is to make research easier to understand cryptography, especially authentication and digital signatures, with the existence of this application it is expected to improve the process of understanding researchers towards authentication and digital hands.